Osobliwości natury a metoda: filozofia naturalna wobec wyjątku siedemnastowiecznej Anglii - Lebek, Karolina (Er(r)go. Teoria - Literatura - Kultura, 2014)
Karolina Lebek Curiosities and Method: Natural Philosophy and Exceptionality in Seventeenth-Century England. The article is concerned with the philosophical function of curiosities in Sir Francis Bacon’s thought, especially his new logic. It takes as its starting point two critiques Bacon launched in his writings, first, of epistemological capabilities of the human mind and, second, of the heretofore methods of studying nature at universities (scholasticism with its uses of the syllogism) and the renaissance court (natural histories with their uses of the emblem). As a separate category of objects and phenomena, curiosities were central for Bacon’s new inductive method as correctives for the flawed mind and thus as regulatory means for inductive interpretation. Such treatment puts curiosities in a paradoxical position of both the object of study and a vital element of the method itself.